Electrochemical behavior of manganese oxides on flexible substrates for thin film supercapacitors. (20th January 2015) - Abdur, Rahim; Kim, Kyungbae; Kim, Jae-Hun; Lee, Jaegab
Highlights: Amorphous MnOx thin films were prepared on flexible substrates by electron beam evaporation. The electrochemical behavior of the MnOx electrode was investigated using cyclic voltammetry. A large potential window was employed to examine the possibility of increased energy density. Potential window for supercapacitor electrodes should be carefully selected by considering the material properties. ABSTRACT: Amorphous MnOx thin films were prepared on flexible substrates by electron beam evaporation, with the aim of using them as electrodes in supercapacitors. The material properties of the MnOx films were characterized by scanning electron microscopy, atomic force spectroscopy, X-ray photoelectron spectroscopy, and Rutherford backscattering spectroscopy. Cyclic voltammetry was then employed to study the electrochemical reaction mechanism. A large potential window was employed (–0.4 to 1.0 V vs. SCE) to investigate the possibility of increased energy density. When the lower potential limit was expanded from 0.0 to –0.4 V vs. SCE, faradaic redox waves were observed in the expanded region, suggesting that the redox reaction was mainly controlled by cation diffusion into the bulk structure. The galvanostatic cycle test demonstrated that capacitance was retained up to 500 cycles for a potential window of –0.1 to 1.0 V vs. SCE.